Effect of doses of vinasse in the cultivation of radish (Raphanus sativus L.), for the ecological control of the earthworm - Gálvez Torres, Edwin (2020)
The research deals with the application of vinasse, which is a by-product in the production of sugar and ethanol from sugarcane juice. The main objective was to determine what dose of vinasse controls the earthworm (Agrotis ipsilon) in the radish crop. The experiment was carried out at the Los Anitos Farm and the Completely Random Block Design was used, which consisted of three blocks and five treatments T1 = 0, T2 = 8, T3 = 16, T4 = 24,T5 = 32 ml / 1;6m2.It is worth mentioning that the dose was 8 ml of vinasse / 24ml of water / 1;6 m2 / week and was applied until the fourth week. The field and laboratory evaluations were carried out and the experimental data was obtained which was then processed with the analysis of variance and the Duncan test at 5 % error. The results determined that T5 stands out in a lower percentage of damage with 24;11 % of affected plants, plant length with 24;28 cm, commercial yield with 7;59tn / ha,weight per plant 37;71 g,weight of bulb 17;86 g and equatorial diameter with 3;02 cm. .